Molecular Tagging of Genes for Brown Planthopper Resistance and Earliness Introgressed From Oryza australiensis Into Cultivated Rice, O. sativa - Ishii, T.; Brar, D.S.; Multani, D.S.; Khush, G.S. (Canadian Science Publishing, 1994)
Restriction fragment length polymorphism analysis was carried out to tag the alien genes for brown planthopper (BPH) resistance and earliness introgressed from wild species Oryza australiensis into cultivated rice, O. sativa L. One introgression line (IR65482-4-136-2-2), resistant to biotypes 1, 2, and 3 of BPH and early in flowering, was selected from BC2F4 of the cross between O. sativa (IR31917-45-3-2) and O. australiensis (accession 100882). Recurrent parent, O. australiensis, and introgression line were surveyed for RFLP using probes of chromosomes 10 and 12. Two probes, RG457 and CDO98, detected introgression from O. australiensis. Cosegregation between introgressed characters and molecular markers was studied in F2 derived from the cross between the introgression line and recurrent parent. The gene for BPH resistance is linked with RG457 of chromosome 12 at a distance of 3.68 ± 1.29 cM, and the gene for earliness is linked with CDO98 of chromosome 10 at a distance of 9.96 ± 3.28 cM. Such close linkage is useful in marker-based selection while transferring BPH resistance from introgression line into other elite breeding lines. Introgression at the molecular level indicates that the mechanism of alien gene transfer is probably genetic recombination through crossing over rather than substitution of whole or large segment of chromosomes of wild species.Key words: molecular tagging, alien gene introgression, rice, wild species, brown planthopper resistance.